Analysis of Social Media Messages on COVID-19 - Patrick Udende; Kaior Samuel Akpede; Rasaq Mohammed Adisa; Ahmad Fahmi Mahamood; Shuhairimi Abdullah; Saudat S. Abdulbaqi; Abubakar Y. Ibrahim; Oba Abdulkadir La’aro (Journal of Human Development and Communication (JoHDeC), 2025)
There is a rich literature on health communication generally. Most of these literatures dwell on diseases and viruses (see Kampf, Todt, Pfaender & Steinermann, 2020). However, rarely is anything found on the emergent virus COVID-19 otherwise known as Corona virus. This gives impetus to the study which aim is to analyse messages people post on social media about the virus. A purposive sampling of selected messages on ASUU Congress Whatsapp platform of Academic Staff Union of Universities, University of Ilorin Chapter was used for the analysis between 1st January and 31st March 2020. Results show that most of the messages were on preventive measures as their hallmark was to create awareness on how to forestall people from being vulnerable to it. The study concludes that outbreak of novel diseases and viruses are bound to emerge, and social media will continue to serve as platforms for people to share messages about emerging diseases and viruses. Among other things, the study recommends sustained use of the social media by people to share not only preventive but also corrective measures about viruses as they emerge.